KEPEMIMPINAN KEPALA SEKOLAH DALAM UPAYA MENINGKATKAN KINERJA GURU - Novia Rani; Agus Sujarwo; An An Andari (UNISAN JURNAL, 2024)
The point of this exploration is to decide the administration of school administrators in further developing educator execution at SDN 2 Beringin Raya, Kemiling Area, Bandar Lampung City. This kind of examination is subjective illustrative exploration. In information assortment methods in this examination, different strategies were utilized, in particular meetings, perception and documentation. The information examination strategy utilized in this exploration is subjective examination. The exploration results show that the Primary's Authority is executed in an arranged, efficient and feasible way. During the execution of management, the important's mentality obviously didn't obstruct the growing experience of Islamic strict schooling in the homeroom, even toward the finish of the example the chief gave inspiration to understudies to steadily review. Islamic Strict Training Educators have great execution in the educational experience. This should be visible from the most common way of getting ready learning plans which are ready as per the models set out in educator execution norms. At the learning execution stage, the educator can dominate the class, ace the material well, then, at that point, the instructor can fluctuate showing strategies and use learning media and give valuable open doors to understudies to cooperate with questions and replies. The issue in executing management of Islamic Strict Training educators in schools is the low inspiration of instructors to complete oversight..